INTEGRATION OF LOCAL WISDOM AND DIGITAL INNOVATIONAS A STRATEGY FOR STRENGTHENING BUSINESS RESILIENCEOF CREATIVE MSMES IN INDONESIA - Zulfikar Victory; Jesica Oktavia; Adeliya Djunaidi; Fauziah Mutiara Thalib (BEMJ: Business, Entrepreneurship, and Management Journal, 2025)
The resilience of creative micro, small, and medium enterprises (MSMEs) has become a critical issue amid accelerating digital transformation and increasing socio-economic uncertainty. This study aims to systematically map the conceptual landscape of integrating local wisdom and digital innovation as a strategy for strengthening business resilience of creative MSMEs in Indonesia, identify research gaps in the last five years, and explore future research opportunities. A Systematic Literature Review (SLR) approach was employed using content analysis of scholarly article abstracts. The findings reveal that existing literature predominantly adopts conceptual and case-based approaches focusing on cultural digitalization, community-based innovation, and adaptive resilience strategies. However, empirical generalization, longitudinal resilience measurement, and integrative theoretical frameworks remain limited. Analysis of TF-IDF trends shows a significant increase in research attention to topics related to marketing innovation and local wisdom in the digital context since 2019, peaking in 2024-2025. This reflects a paradigm shift where local wisdom is no longer seen as contradictory to modernity but as a crucial contextual foundation for digital innovation. Nevertheless, research focus remains fragmented across specific sectors such as tourism and creative agriculture without comprehensive conceptual synthesis. This study contributes by providing a structured conceptual map, identifying key research gaps, and proposing future research directions including the development of more integrative theoretical frameworks and diverse methodological approaches such as longitudinal studies and mixed methods. The findings also offer practical implications for policymakers and practitioners in designing targeted support programs for creative MSMEs.